ANALISA KERENTANAN SIS.TRISAKTI.AC.ID MENGGUNAKAN TEKNIK VULNERABILITY SCAN - Is Mardianto; Agung Sedyono; Ahmad Hafzan (Website, 2015)
Security means freedom from the fear of losing the object, his or her secret known to others. According to the terminology of US DoD 2011, Information Security (InfoSec) is safeguardsfor information and information systems, from someone’s access or unauthorized information modification that occurs on storage media or data transmission. The purpose of this study is to determine the